On not being someone else : tales of our unled lives - Miller, Andrew H., 1964- (Cambridge, Massachusetts : Harvard University Press, 2020)
'The alternate self is a persistent theme of modern culture. From Robert Frost to Sharon Olds, Virginia Woolf to Ian McEwan, poets and novelists-and readers-are fascinated by paths not taken. In an elegant and provocative rumination, Andrew H. Miller lingers with other selves, listening to what they have to say about our stories and our lives'--
One person, two roads -- Tales of our adulthood -- All the difference.
Includes bibliographical references and index.
Keywords: Self in literature; Existentialism in literature; Identity (Psychology) in literature